IQRA SEBAGAI PILAR LITERASI ISLAM: MENJAWAB TANTANGAN DISINFORMASI DAN HOAKS DI ERA DIGITAL - Dona Hariati; Hidayat Ma'ruf; Hamdan; Ridhahani Fidzi (Adisam Publisher, 2025)
In the digital age, unfiltered information flows trigger the spread of hoaxes and disinformation, including in a religious context. This article examines the concept of Iqra in Islam as the foundation of literacy, which encompasses not only the ability to read, but also understanding, analysis, and critical attitudes towards information. This study uses a qualitative approach based on literature review, with the main sources being verses from the Qur'an, hadith, and contemporary literature on digital literacy. The results of the study indicate that Iqra is a relevant literacy principle for developing tabayyun, critical thinking, and ethical awareness in responding to information. Understanding Iqra can be a strategic solution in shaping a literate, selective, and wise Muslim society amid digital challenges. This article recommends strengthening Islamic education based on spiritual literacy values as a response to the threat of hoaxes and the degradation of religious understanding.